USING ENTREPRENEURSHIP TO IMPROVE THE WELL-BEING OF THE POPULATION - Yusufaliyev Olimjon Abdurakhmonovich (PhD) (Ecominds Press, 2025)
This article examines the improvement of the methodology for using entrepreneurship to improve the well-being of the population in terms of an important factor in poverty reduction.
Keywords: Entrepreneurship, well-being of the population, poverty reduction, methodology, improvement.